The Relationship Of Family Support With The Liveliness Of The Following Gymnastics In Patients With Diabetes Mellitus Type DuaDi Club Prolanis Diamen Barigas BPJS Office Palangka Raya - Untung Halajur; Sri Widya; Aida Kusnaningsih (CV. Inara, 2022)
Physical exercise is one of the pillars of diabetes management that needs to be cultivated, because there are many benefits that can be felt by people with DM. The number of benefits that can be felt by patients with DM, it is very necessary activeness of DM patients in doing one gym gymnastics. Activity of DM patients can also be influenced by several factors one of which is family support. This study aims to determine whether there is a relationship of family support with the activity of following gymnastics in people with diabetes mellitus type two. Thisused study observational research Cross Sectional. Instruments include family support questionnaires and liveliness forms. The population in this study were members of Club Prolanis Diamen Barigas BPJS Office Palangka Raya who experienced DM and samples in the study were two types of DM patients who followed the gymnastics activities as much as 30 respondents using sampling technique that is total sampling. Univariate analysis using frequency distribution table and bivariate analysis usingtest Chi-Square. The results showed that there was a significant correlation between family support and activeness following gymnastics in patients with type 2 diabetes mellitus At Club Prolanis Diamen Barigas BPJS Office Palangka Raya, with the result of statistical test of continuity correction known that significance p value of 0,046 with α < (0.05). There is a relationship between family support and active follow gymnastics in patients with type 2 diabetes mellitus at Club Prolanis Diamen Barigas BPJS Palangka Raya.